Phân tích đa thức thành nhân tử: (3x-5)^2-(5x+2)^2

Phân tích đa thức thành nhân tử:
(3x-5)^2-(5x+2)^2

0 thoughts on “Phân tích đa thức thành nhân tử: (3x-5)^2-(5x+2)^2”

  1. Đáp án:

    (3x – 5)² – (5x + 2)²

    = [3x 5 (5x + 2)][3x 5 + (5x + 2)]

    = (3x 5 5x 2)(3x 5 + 5x + 2)

    = [(3x – 5x) + (-5 – 2)] . [(3x + 5x) + (-5 + 2)]

    = [2x + (7)] . [(8x + (3)]

    = (2x 7)(8x 3)

    @Yết gửi bạn nhé~~

    HỌC TỐT~~

    #NOCOPY

    #NOTHINGISIMPOSSIBLE

    Reply
  2. Giải thích các bước giải:

    $(3x-5)^2-(5x+2)^2$

    $=[3x-5- (5x+2)][3x-5+(5x+2)]$

    $=(3x-5-5x-2)(3x-5+5x+2)$

    $=(-2x-7)(8x-3)$

    $=-(2x+7)(8x-3)$

    Học tốt!!!

    Reply

Leave a Comment